Physical activity levels associated with insomnia and depressive symptoms in middle-aged and elderly patients with chronic schizophrenia - Liu, Zhiwei; Zhang, Yulong; Sun, Liang; Wang, Juan; Xia, Lei; Yang, Yating; Sun, Feng; Li, Wenzheng; Yao, Xianhu; Yang, Rongchun; Liu, Huanzhong (Frontiers in Psychiatry, 2023)
Background Previous evidence suggested that physical activity had beneficial effects on psychopathological symptoms, insomnia, or depressive symptoms in people with schizophrenia. This study investigated the association between physical activity levels and insomnia and depressive symptoms in middle-aged and elderly hospitalized patients with chronic schizophrenia (CS). Methods 179 participants were enrolled. We used the 30-item Positive and Negative Syndrome Scale (PANSS–30) to assess the psychopathological symptoms. We used the Insomnia Severity Index scale (ISI) and 17-item Hamilton Depression Scale (HAMD-17) to evaluate insomnia and depressive symptoms. Daily physical activity time less than 30 min, within 30–60 min, and more than 60 min were defined as physical inactivity, moderate physical activity, and vigorous physical activity, respectively. The Chi-square test, analysis of variance (ANOVA), and Mann–Whitney U-test were applied for categorical, continuous, and non-normal distribution variables, respectively. The Pearson or Spearman’s correlation analyses were utilized to examine the association between physical activity levels, ISI total scores, HAMD total scores, and socio-demographic and clinical variables. Finally, socio-demographic variables with a P-value < 0.05 in the comparison between insomnia/depressive group and non-insomnia/depressive group were considered for inclusion in binary logistic regression analysis to determine the relationship between physical activity levels and insomnia or depressive symptoms. Results The ISI total scores (r = –0.247, P = 0.001) and HAMD total scores (r = –0.312, P < 0.001) were negatively correlated with physical activity levels. Logistic regression analysis revealed that older age, higher depressive factor scores, and lower physical activity level were influential factors of insomnia symptoms in CS patients (P < 0.05). In addition, vigorous physical activity (compared with physical inactivity) and higher negative and depressive factor scores were independently associated with depressive symptoms in CS patients (P < 0.05). Conclusion Physical activity levels were influential factors in comorbid insomnia and depressive symptoms in CS patients. Given the benefits of physical activity, it should be strengthened as a routine adjunct to clinical treatment or psychiatric care so as to improve the physical and mental health of patients with psychiatric symptoms.